Cotties of fuel and lubricants in Central Asia as a result of integration factors - A. М. Maratov; K. A. Ajekbarov; T. K. Kamchybekov (Путеводитель предпринимателя)
The work discusses the levels of fuel and lubricants in the CU countries and the factors of the formation of prices for them of the Kyrgyz Republic in the context of integration in the EAEU (Eurasian Economic Union) are represented. Fuel and lubricants, as a basic product, are a key factor in the price level for all types of goods and services. Quotes of fuel and lubricants in the CA countries, which are part of and not part of the EAEU, differ significantly. And the reason for this is not only the ratio of the volume of production and consumption of fuel and lubricants in each of them, but also tax, customs, tariff norms in these countries and the EAEU. Sufficient production of fuel and lubricants in the Union was noted in Belarus, Russia and Kazakhstan. From the republics of the CAA, only Turkmenistan can fully provide their economies with fuel and lubricants. The Kyrgyz Republic will have to take system measures to reduce dependence on the import of fuel and lubricants, by increasing the volume of their production, developing electric transport and overcoming the generation of electricity generation.